Primary evidences on the robustness of environmental accounting from emergy - Giannetti, B.F.; Almeida, C.M.V.B.; Agostinho, F.; Bonilla, S.H.; Ulgiati, S. (Journal of Environmental Accounting and Management, 2026)
Agricultural systems operate in the interface between environment and human economy, combining the use of natural and purchased resources in food production. With the aid of the ternary diagram, data of agricultural systems taken from literature are organized in order to evidence the influence of the type of culture and of the analyst’s criteria on the results of environmental accounting in emergy. All the systems represented in the ternary diagram determine a qualitatively well-defined region, less or more extended according to the case. Points defined for the emergy coordinates were localized in defined regions observed in the diagram. Emergy accounting is presented as a method able to environmentally characterize production systems in a robust way, even with variations in analyst’s criteria and data nature or origin. It is shown that the results of environmental accounting obtained with the use of the emergy methodology are only slightly influenced by the analyst’s criteria. On the other hand, the ternary diagram appears as an interesting graphical tool to determine finding and checking robustness of emergy accounting. The robustness of emergy methodology is remarkable.